A method for evaluation of both aerobic and anaerobic capacities of middle- and long-distance runners - Mitsuka, T.; Tsuji, T.; Nabekura, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
An individual`s anaerobic capacity is evaluated in terms of the maximal accumulated oxygen deficit in the supramaximal test. The present study was conducted to validate the method used for evaluation of anaerobic capacity using an index calculated from the aerobic test (a submaximal test conducted 5 or 6 times in 3-minute stages and a maximal test of 4-6 minutes). Seventeen well-trained Japanese middle- and long-distance runners including elite athletes participated in the aerobic test on one day and in the supramaximal test of 2-4 minutes on another day. The mean accumulated oxygen deficit in the maximal test was 30.6 ± 10.0 mlO2/kg, and the mean maximal accumulated oxygen deficit in the supramaximal test was 55.7 ± 16.1 mlO2/kg. There was a significant positive relationship between accumulated oxygen deficit and the maximal accumulated oxygen deficit (r=0.82, p<0.001). A stronger positive relationship between the above 2 parameters was evident in 10 middle distance runners (r=0.94, p<0.001). These results suggest that maximal accumulated oxygen deficit can be evaluated in terms of the accumulated oxygen deficit in the maximal test.